The Influence of Quality of Services and Infrastructures on Inpatient Satisfaction - Nunti Sibuea; Bobby Indra Prayoga; Ari Kartiko; Arsyawina Arsyawina (Majapahit Journal of Islamic Finance and Management, 2021)
This research was conducted at the Mother and Child Hospital “Fatimah” Lamongan with a scope of marketing which consists of service quality variables (X1), Infrastructure (X2) and patient satisfaction (Y). The study uses quantitative method. The population is the inpatients of the Mother and Child Hospital “Fatimah” Lamongan which will then be selected as the research sample. The data collection technique used a questionnaire and the sampling technique used probability sampling, with a random sampling technique and 98 patients were selected as samples. It uses primary data obtained directly from the respondents. The data obtained have tested the validity and reliability using SPSS software. The analysis of hypothesis testing used multiple linear regression analysis techniques and the results obtained that the quality of services and infrastructure have a significant effect on patient satisfaction inpatient care at the “Fatimah” Lamongan Mother and Child Hospital, while the variable infrastructure has a dominant influence on inpatient satisfaction.